The Impact of COVID‐19 on Psychotherapy Participation Among Individuals With Posttraumatic Stress Disorder Enrolled in Treatment Research. Issue 1 (22nd July 2021) - McLean, Carmen P.; Back, Sudie E.; Capone, Christy; Morland, Leslie; Norman, Sonya B.; Rauch, Sheila A. M.; Schnurr, Paula P.; Teng, Ellen; Acierno, Ron
Abstract: The onset of the COVID‐19 pandemic disrupted many aspects of daily life and required a rapid and unprecedented shift in psychotherapy delivery from in‐person to telemental health. In the present study, we explored the impact of the pandemic on individuals' ability to participate in posttraumatic stress disorder (PTSD) psychotherapy and the association between the impact of COVID‐19 impact on health and financial well‐being and psychotherapy participation. Participants ( N = 161, 63.2% male, M age = 42.7 years) were United States military veterans ( n = 108), active duty military personnel ( n = 12), and civilians ( n = 6), who were participating in one of nine PTSD treatment trials. The results indicate a predominately negative COVID‐19 impact on therapy participation, although some participants (26.1%) found attending therapy sessions through telehealth to be easier than in‐person therapy. Most participants (66.7%) reported that completing in vivo exposure homework became harder during the pandemic. Moreover, the impact of the pandemic on PTSD symptom severity and daily stress were each associated with increased difficulty with aspects of therapy participation. The findings highlight the unique challenges to engaging in PTSD treatment during the pandemic as well as a negative impact on daily stress and PTSD severity, both of which were related to treatment engagement difficulties.